FINANCIAL RISK MANAGEMENT WITHIN NATIONAL COMPANIES - Villalba Clara Melisa, Guerreño; Barreto Jessica Diana, Varela (Revista Gênero e Interdisciplinaridade, 2023)
The research presented is entitled, “Financial risk management” as a general objective is to analyze the current situation of companies based in Ciudad del Este, to face unexpected financial risks. The approach is quantitative, the information was collected through an online survey and the questionnaire was used as an instrument. The population corresponds to 100 companies from different sectors, from the San José neighborhood of Ciudad del Este. The field study is carried out in 20 companies, 20 administrators of the corresponding 20% of the population have been taken as a sample. The results released from the surveys have made it possible to achieve the objectives proposed in the investigation. It is concluded that most companies do not have financial risk management, that is, they do not have a financial fund against possible risks. A minority affirm that they have no knowledge on the subject. As for another minority, they have stated that they do have resources such as financial funds within their company and that they do have financial risk management.